PENGEMBANGAN JIWA ENTERPRENEURSHIP PADA MAHASISWA PRODI MPI MELALUI MATA KULIAH EDUPRENEURSHIP: STUDI KASUS DI STIT MUHAMMADIYAH TEMPURREJO NGAWI - Fatonah, Kuni (LPPM STAI Muhammadiyah Probolinggo, 2025)
The digital era and the evolving world of work demand that students not only rely on theoretical knowledge but also develop an entrepreneurial spirit. The Islamic Education Management Study Program at STIT Muhammadiyah Tempurrejo Ngawi responds to this need through the Edupreneurship course, designed to foster students' entrepreneurial character and skills. The purpose of this study was to analyze the role of the Edupreneurship course in building the mindset and developing entrepreneurial competencies in MPI students. The study used a qualitative approach with a case study method. Data were obtained through observations of the learning process and interviews with lecturers and students. The results showed that the Edupreneurship course successfully developed students' entrepreneurial spirit through theory and practice, such as creative product development, business simulations, and business plan development. Students experienced improvements in creativity, independence, and risk-taking. Factors driving success included applicable teaching methods, internal student motivation, and supportive campus facilities. Challenges faced included students' limited business experience and limited access to capital. These findings indicate the importance of strengthening entrepreneurship within the curriculum and optimizing hands-on practice to better prepare students to become entrepreneurs in the educational field.